Moderation of the association between COVID-19-related income loss and depression by receipt of financial support: Repeated cross-sectional surveys of young adults in Canada and France (2020–2021). (March 2023) - Coulaud, Pierre-julien; Salway, Travis; Jesson, Julie; Bolduc, Naseeb; Ferlatte, Olivier; Bertrand, Karine; Desgrées du Loû, Annabel; Jenkins, Emily; Jauffret-Roustide, Marie; Knight, Rod
Abstract: Background: To mitigate the adverse effects of the COVID-19 pandemic on financial resources, governments and family/friends mobilized financial support interventions (e.g., emergency aid funds) and assistance. However, little is known about how financial assistance alleviated mental health problems. This study aimed to investigate the moderating effect of financial support from the government or from family/friends on the association between income loss and depression among young adults. Methods: Two online cross-sectional surveys among young adults ages 18–29 living in Canada and France were conducted in 2020 (n = 4, 511) and 2021 (n = 3, 329). Moderate-to-severe depressive symptoms were measured using the Patient Health Questionnaire-9 (cut-off score: ≥10). Two logistic regression models were performed for each survey with an interaction term between income loss and financial support (government or family/friends modeled separately), controlling for demographics. Results: Overall, half reported depressive symptoms (2020/2021: 53.5%/45.6%), and over a third lost income (2020/2021: 10.2%/11.6% all income, 37.7%/21.6% some income). In 2020, 40.6% received government financial support (17.7% in 2021) while family/friends support was received by 12% (in both surveys). In both surveys, among those who received governmental financial support, income loss was associated with depression, whether participants lost all their income (e.g., 2020: Adjusted Odds Ratios (AOR) 1.75, 95% Confidence Interval [1.29–2.44]), or some of their income (e.g., 2020: AOR 1.45 [1.17–1.81]). However, among those who received family/friends financial support, income loss was no longer significantly associated with depression in both cycles, whether participants lost all their income (e.g., 2020: AOR 1.37 [0.78–2.40]), or some of their income (e.g., 2020: AOR 1.31 [0.86–1.99]). Conclusions: Association between income loss and depression was moderated by receipt of family/friends financial support but not by receipt of government financial support. Financial support interventions may help to mitigate the negative effects of income loss on young adults mental health during periods of economic crisis. Highlights: Young adults' finances have been adversely affected by the COVID-19 economic crisis. Those who lost income and received family financial support had lower risk of depression. No protective effect was found for those who received governmental financial support. Adequate financial support may have a positive effect on youth mental health.